(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The integration of informatics into primary education is becoming increasingly significant in the modern digital era, where technological literacy is recognized as an essential component of a child’s intellectual development. This article explores the methodologies of teaching informatics in primary schools, with a focus on pedagogical approaches, didactic principles, and the psychological characteristics of young learners. The study emphasizes that introducing informatics at an early stage not only familiarizes pupils with fundamental concepts of information technology but also fosters logical thinking, creativity, and problem-solving abilities. Informatics education at the primary level requires a delicate balance between theoretical knowledge and practical application. Therefore, the article discusses age-appropriate teaching methods, including play-based learning, interactive exercises, digital games, project-based tasks, and the use of multimedia resources. Special attention is paid to the adaptation of complex informatics topics into simple, comprehensible forms that align with children’s cognitive abilities. The role of the teacher as both a facilitator and guide is highlighted, demonstrating how effective classroom management, motivational strategies, and individualized learning approaches can enhance students’ engagement and comprehension. The article also examines the challenges faced in teaching informatics to primary school students, such as limited access to digital tools, lack of specialized teaching materials, and the need for continuous teacher training. Possible solutions are proposed, including the integration of national curriculum standards, the use of open-source educational platforms, and collaboration between schools and families in creating a supportive digital learning environment. Ultimately, the research concludes that effective teaching methodologies in primary school informatics contribute not only to digital literacy but also to the holistic development of students, preparing them for active participation in the knowledge-based society. By equipping children with essential skills in information processing, algorithmic thinking, and responsible digital behavior, primary education lays the foundation for lifelong learning in the field of information technology.